Comparative study of serum protein binding to three different carbon-based nanomaterials. (December 2015) - Sopotnik, Maja; Leonardi, Adrijana; Križaj, Igor; Dušak, Peter; Makovec, Darko; Mesarič, Tina; Ulrih, Nataša Poklar; Junkar, Ita; Sepčić, Kristina; Drobne, Damjana
Abstract: Nanomaterials (NM) that enter a biological environment are immediately covered by a layer of proteins, which form a protein corona that governs further interactions of NM within the organism. In this study, we investigated the bovine serum albumin corona and the human serum protein corona, formed on three different carbon-based NM: carbon black, multi-walled carbon nanotubes, and graphene oxide. The serum protein corona of all three studied NM was found to be enriched with complement factors and apolipoproteins. In addition, by measuring the enzymatic activity of the serum butyrylcholinesterase, we have shown that also less abundant proteins could be included in and affected by the corona formation. The studied NM show NM-specific affinities towards albumin binding, both in the pure bovine serum albumin solution or in the human serum. Interestingly, graphene oxide has the lowest affinity towards albumin, but it shows the highest sorptive capacity for other serum proteins, including those present in small amounts.